2021
DOI: 10.1016/j.isci.2021.102511
|View full text |Cite
|
Sign up to set email alerts
|

Lemon exosome-like nanoparticles enhance stress survival of gut bacteria by RNase P-mediated specific tRNA decay

Abstract: Diet and bile play critical roles in shaping gut microbiota, but the molecular mechanism underlying interplay with intestinal microbiota is unclear. Here, we showed that lemon-derived exosome-like nanoparticles (LELNs) enhance lactobacilli toleration to bile. To decipher the mechanism, we used Lactobacillus rhamnosus GG (LGG) as proof of concept to show that LELNs enhance LGG bile resistance via limiting production of Msp1 and Msp3, resulting in decrease of bile accessibility to cell membrane. Furthermore, we … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
26
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 41 publications
(34 citation statements)
references
References 42 publications
1
26
0
Order By: Relevance
“…54 Increased levels of Clostridium bacteria boost the inflammatory reaction and oxidative stress in the circulation and suppression of Clostridium bacteria could suppress the production of harmful products from the intestine into the circulation and down-regulate the occurrence of inflammation and oxidative stress. 55 Fusicatenibacter and Clostrodium were positively correlated with FBC level. Both are favorably connected with oxidative stress and inflammatory response, while glucose metabolism and antioxidant enzyme activity are negatively correlated.…”
Section: Gut Microbiotamentioning
confidence: 87%
See 1 more Smart Citation
“…54 Increased levels of Clostridium bacteria boost the inflammatory reaction and oxidative stress in the circulation and suppression of Clostridium bacteria could suppress the production of harmful products from the intestine into the circulation and down-regulate the occurrence of inflammation and oxidative stress. 55 Fusicatenibacter and Clostrodium were positively correlated with FBC level. Both are favorably connected with oxidative stress and inflammatory response, while glucose metabolism and antioxidant enzyme activity are negatively correlated.…”
Section: Gut Microbiotamentioning
confidence: 87%
“…The increased level of Clostridium in the intestine precipitates inflammatory reactions in diabetics 54 . Increased levels of Clostridium bacteria boost the inflammatory reaction and oxidative stress in the circulation and suppression of Clostridium bacteria could suppress the production of harmful products from the intestine into the circulation and down‐regulate the occurrence of inflammation and oxidative stress 55 . Fusicatenibacter and Clostrodium were positively correlated with FBC level.…”
Section: Discussionmentioning
confidence: 99%
“…Besides, PELNs show microbiome regulatory properties through the promotion of the growth of probiotics. Lemon-derived ELNs protect LGG from bile possibly through inhibition of the expression of Msps protein, induction of specific bacterial tRNA decay, and inhibition of S.24-7 growth (93). Lemon-derived ELNs…”
Section: Modulation Of Microbiota Compositionmentioning
confidence: 99%
“…(B) Modulate microbiota: PELNs inhibit pathogenic bacteria such as P. gingivalis through PA binding to HBP35 (19). PELNs protect probiotics through decay tRNA in probiotics (93). PELNs transform miRNA to microbiota, which has the potential to modulate oral microbiota.…”
Section: Periodontal Tissue Regenerationmentioning
confidence: 99%
“…At the same time they also possess miR7267-3p which helps in proliferation of LGG in gut. Whereas Lemon derived ELNs enhances bile resistance in LGG by limiting the expression of Msp1 or Msp2 genes and also manipulates Streptococcus thermophilus ST-21 (STH) mitigates Clostridioides difficile infections (CDI) which is a leading cause of antibiotic resistant colitis 50 , 51 . A pre- clinical study in diet- induced mice models has shown therapeutic aspects of Orange derived ELNs (OELNs) that mainly targets microsomal triglyceride transfer protein (MTP) and angiopoietin-like protein-4 (ANGPTL4) and reduces the lipid absorption as well as inflammation in gastrointestinal lining.…”
Section: Cargoes Of Edible Exosome-like Nanoparticlesmentioning
confidence: 99%